LAD-PARDA BASICS IN BUKHARA SHASHMAKAM - Muyassarkhan Achildieva Adiljanovna; Ikromova Farangis Yigitali qizi (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2022)
This article provides information on the basics of Bukhara Shashmakam. In addition, the issue of lad in makams is one of the topical issues in makam studies today. From this point of view, opinions and comments are described in detail on the laws of Shashmakam lad-scale, which is the golden treasure of our musical art.